Tri Hita Karana as a Moderator of Green Intelectual Capital and Green Innovation on Sustainable Performance - Atim Purwaningrat; Luh Nik Oktarini; Ida I Dewa Ayu Yayati Wilyadewi (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
The development of MSMEs in Denpasar City experiences significant growth every year. Economic profits from business activities are expected to result in improved living conditions globally, but can also lead to environmental damage and social inequality. Sustainable business is a business effort to minimize negative impacts on the environment and social so that future generations have adequate resources. Tri Hita Karana is local wisdom which aims to achieve happiness by prioritizing the principles of togetherness, harmony and balance between economic motives, environmental preservation, culture, aesthetics and spirituality. This research aims to determine the influence of Green Intellectual Capital and Green Innovations on the Sustainable Performance of MSMEs in Denpasar City with Tri Hita Karana as moderator. This research was carried out on MSMEs in Denpasar City, a sample of 100 people with a sampling technique using probability sampling. The data analysis technique used is the Partial Least Square (PLS) method. The results show that hypotheses 1 and 2 are accepted, namely that green intellectual capital and green innovation have a positive and significant relationship with sustainable performance. Tri Hita Karana does not have a significant effect on the relationship between green intellectual capital and sustainable performance and does not have a significant effect on the relationship between green innovation and sustainable performance, which means that hypotheses 3 and 4 are rejected.